Analysis Of Financial and Income Disparity Between Rural-Urban Areas In Indonesia - Yuni Andari (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2020)
The purpose of this study is to analyze the factors that affect income disparity between rural-urban areas in Indonesia and to analyze the effect of financial development on economic inequality. The research method used is a quantitative descriptive analysis using multiple linear regression of panel data during the period of 2014-2017. The dependent variable in this study is the difference in income between rural and urban using differences in the amount of rural and urban expenditure as a proxy. The independent variables consist of financial depth scale with total bank assets as a proxy, financial activity withthe amount of agricultural credit as a proxy, and financial efficiency with the ratio of loan to deposit as a proxy. Other control variables are also analyzed including per capita income, government spending, level of education and trade openness. The results of the study showed that the effect of total bank assets on income disparity between rural and urban areas was positive and significant, while the effect of agricultural credit and the ratio between credit to bank deposits did not significantly influence income disparity between rural and urban areas. Government spending, per capita income and education have a positive and significant effect on income disparity between rural and urban areas. Meanwhile, net export as a proxy of regional economic openness data does not significantly influence income disparity. Based on the results of the study, the policy implications that can be recommended to reduce income inequality between rural-urban areas are through increasing the scale of banking finance, increasing government spending on rural areas, increasing the education of rural communities and increasing income per capita